Protective Effects of a Human 18-Kilodalton Cationic Antimicrobial Protein (CAP18)-Derived Peptide against Murine Endotoxemia - Kirikae, Teruo (American Society for Microbiology, 1998)
CAP18 (an 18-kDa cationic antimicrobial protein) is a granulocyte-derived protein that can bind lipopolysaccharide (LPS) and inhibit various activities of LPS in vitro. The present study examined the protective effect of a synthetic 27-amino-acid peptide (CAP18(109–135)) from the LPS-binding domain of CAP18 against antibiotic-induced endotoxin shock, using highly LPS-sensitive d-(+)-galactosamine (d-GalN)-sensitized C3H/HeN mice. The antibiotic-induced endotoxin (CAZ-endotoxin) was prepared from the culture filtrate of Pseudomonas aeruginosa PAO1 exposed to ceftazidime (CAZ). Injection of CAP18(109–135) protected the mice injected with LPS or CAZ-endotoxin from death and lowered their tumor necrosis factor (TNF) levels in serum in a dose-dependent manner. Treatment with CAZ caused death of the d-GalN-sensitized P. aeruginosa PAO-infected mice within 48 h, while injection with CAP18(109–135) rescued the mice from death. In the mice rescued from death by injection with CAP18(109–135), endotoxin levels in plasma and TNF production by liver tissues were decreased but the numbers of viable infecting bacteria in their blood were not decreased significantly and remained at the levels in CAZ-treated mice. These results indicate that CAP18(109–135) is capable of preventing antibiotic-induced endotoxic shock in mice with septicemia and that the effect is due to its LPS-neutralizing activity rather than to its antibacterial activity.